1987
DOI: 10.1021/bi00398a057
|View full text |Cite
|
Sign up to set email alerts
|

Electron-nuclear coupling in nitrosyl heme proteins and in nitrosyl ferrous and oxy cobaltous tetraphenylporphyrin complexes

Abstract: Electron spin echo envelope modulation (ESEEM) spectroscopy has been used to study electron-nuclear interactions in the following isoelectronic S = 1/2 complexes: NO-FeII(TPP) (TPP = tetraphenylporphyrin) with and without axial nitrogenous base, nitrosylhemoglobin in R and T states, and O2-CoII(TPP) with and without axial base. Only the porphyrin pyrrole nitrogens contribute to the ESEEM of the 6-coordinate nitrosyl FeII(TPP) complexes, nitrosylhemoglobin (R-state), and the nitrosyl complexes of alpha and beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 53 publications
1
54
1
Order By: Relevance
“…(Poorly-resolved spectral components arising from coupling to pyrrole 14N were also identified.) The ESEEM spectral features of oxyCoMb, however, appear at lower frequencies than those of the model compounds recorded at similar magnetic field settings, suggesting smaller hyperfine and/or nuclear quadrupole coupling to the directly coordinated 14N of the proximal histidyl imidazole (Magliozzo & Peisach, 1992). A computer simulation (discussed in detail below) of the spectrum yielded an isotropic hyperfine coupling (4,0) of 2.46 MHz (Figure IB).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…(Poorly-resolved spectral components arising from coupling to pyrrole 14N were also identified.) The ESEEM spectral features of oxyCoMb, however, appear at lower frequencies than those of the model compounds recorded at similar magnetic field settings, suggesting smaller hyperfine and/or nuclear quadrupole coupling to the directly coordinated 14N of the proximal histidyl imidazole (Magliozzo & Peisach, 1992). A computer simulation (discussed in detail below) of the spectrum yielded an isotropic hyperfine coupling (4,0) of 2.46 MHz (Figure IB).…”
Section: Resultsmentioning
confidence: 89%
“…The ESEEM spectrum of oxyCoMb is analogous to the spectra of hexacoordinated oxyCoTPP model compounds containing substituted imidazole as an axial ligand (Magliozzo et al, 1987). The study of models containing pyridine or imidazole demonstrated that the spectral components from axial bases arose from the coupling to the directly coordinated 14N.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Spectroscopic techniques that have been utilized to characterize nitrosylheme proteins include magnetic circular dichroism (MCD) [168,169], infrared (IR) [134,[170][171][172][173][174], resonance Raman (RR) [43,[175][176][177][178][179][180], Mössbauer [181][182][183][184][185], and EPR spectroscopies [61,134,150,[186][187][188][189][190][191][192][193][194][195][196][197][198][199][200]. MCD has been used to characterize the protein-provided axial ligand bound to both Fe(II) and Fe(III) forms of various heme proteins, using the NO, CO, phosphine, and other adducts to develop MCD spectra that are unique for the fifth (protein-provided) ligand [168,169].…”
Section: Nitric Oxide Reactivity With Heme Centersmentioning
confidence: 99%